Altered vascular permeability but not angiogenesis may play a role in the epileptogenesis of human hippocampal sclerosis. Issue 3 (29th July 2021) - Mhatre, Radhika; Anita, Mahadevan; Phillip, Mariamma; Saini, Jitender; Arimappamagan, Arivazhagan; Bharath, Rose Dawn; Chowdary, Ravindranadh M.; Kenchaiah, Raghavendra; Ajay, Asranna; Jamuna, Rajan; Sadashiva, Nishanth; Malla, Bhaskara Rao; et al.
Abstract: Objective . We investigated the role of angiogenesis and vascular permeability in the pathogenesis of human drug‐resistant epilepsy due to hippocampal sclerosis. Methods . Resected hippocampi from 30 histologically confirmed cases of hippocampal sclerosis and 30 age‐matched post‐mortem controls were examined by immunohistochemical quantitation of vascular endothelial markers, CD31 and CD105 (markers of newly formed vessels), and data were analysed relative to MR volumetry. The blood‐brain barrier was evaluated based on immunohistochemistry for IgG, albumin, VEGF and AQP4. Results . Mean vascular density in the hippocampus was 8.71/mm 2 in hippocampal sclerosis samples compared to 7.94/mm 2 in age‐matched controls. No statistically significant increase in vascular density was found in hippocampal sclerosis samples. Although no neoangiogenesis was found in hippocampal sclerosis samples based on CD105, breakdown of the blood‐brain barrier, enhanced neuronal expression of VEGF, and perivascular seepage of IgG and albumin with uptake within neurons and astrocytes were found. Redistribution of the water channel protein, AQP4, reflected by change from normal punctate labelling to intense diffuse staining in hippocampal sclerosis samples, indicated an altered glia‐vascular interface, disrupting blood‐brain barrier permeability. Significance. Our data show no objective histological evidence of angiogenesis in hippocampal sclerosis samples. When controlled for the confounding variable of hippocampal area, there was no difference in vascular density between cases and controls. A leaky blood‐brain barrier and redistribution of AQP4 were identified which may contribute to epileptogenesis. This constitutes the largest study in the published literature evaluating a role of vascular permeability and angiogenesis in human hippocampal sclerosis.